FINANCIAL PERFORMANCE OF SHARIA COMMERCIAL BANKS IN INDONESIA - Taudlikhul Afkar; Widiar Onny Kurniawan; Fauziyah; Ferry Hariawan; Nurin Putri Andini (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
The financial performance of Islamic banks with profitability is a benchmark for success in managing finances in good conditions or under financial pressure. The purpose of this study is to explain the financial performance of Islamic banks in Indonesia during and after the Covid-19 pandemic. This research method uses a quantitative approach with paired sample t-test analysis techniques to analyze differences in financial performance during and after the covid-19 pandemic. The population in this study is 14 Islamic commercial banks in Indonesia, this number is also used as a research sample with saturated sample technique because the number is relatively small. The data used are the combined financial statements of Islamic commercial banks in Indonesia during the covid-19 pandemic, namely 2021-2022 and after the covid-19 pandemic in 2023-2024. The tool used to help with the analysis is JAMOVI.